Association of low T3 level with increased in-hospital mortality in patients with stress cardiomyopathy. Issue 10 (5th November 2021) - Kwon, Seong Soon; Bang, Duk Won; Park, Byoung-Won; Lee, Min-Ho; Hyon, Min-Su; Lee, Seong Soo; Park, Suyeon
Abstract: Background: Stress cardiomyopathy (SCMP) is an acute but reversible heart failure syndrome with varying clinical outcomes. Although low triiodothyronine (T3) levels are closely associated with heart failure, it is uncertain whether total T3 levels on admission might be correlated with clinical outcomes in patients with SCMP. The aim of this study was to investigate the prognostic value of total T3 level for in-hospital mortality in patients with SCMP. Methods: Patients presenting with SCMP at a single tertiary hospital between January 2013 and May 2019 were retrospectively reviewed. The diagnosis of SCMP was confirmed using the International Takotsubo Diagnostic Criteria and echocardiography was performed at least twice at the time of admission. Comorbidities, antecedent triggers, and other cardiac and metabolic parameters were measured in the survivor group compared with the non-survivor group. We evaluated the correlation between these parameters, especially total T3 and the prevalence of in-hospital mortality and the predictive values of total T3. Results: Of the 134 SCMP patients (69.4 ± 15.5 years old, 94 women), 29 (21.6%) died during hospitalisation. The median follow-up period (interquartile range) was 480 days (63.25–1052.50). Total T3 levels were significantly lower in the non-survival group than in the survival group (33.38 ± 22.58 ng/dL vs. 65.72 ± 34.68 ng/dL, p  < 0.0001). Receiver operating characteristic curve analysis showed the cut-offs of total T3 levels (≤64.37 ng/dL) for in-hospital mortality (area under curve [AUC] = 0.764, p  < 0.001). In multivariable analysis, the T3 level (odds ratio [OR], 0.957; 95% confidential interval [CI], 0.934 to 0.982; p  < 0.001), left ventricular ejection in follow-up echocardiography (OR, 0.935; 95% CI, 0.889–0.983; p  = 0.008), and shock at initial presentation (OR, 3.389; 95% CI, 1.076–10.669; p  = 0.037) were independent predictors for in-hospital mortality in SCMP patients. In patients with low T3 (<64.37 ng/dL), the 30-day survival rate was also significantly lower (81.58 vs. 100%, Log rank p  = 0.001). Conclusions: Lower levels of total T3 were strongly correlated with in-hospital mortality in patients with SCMP. A low T3 level might suggest poor prognosis in patients with SCMP.